STRATEGI PENGEMBANGAN OBJEK WISATA PANTAI SUMEDANG DI KECAMATAN RANAH PESISIR KABUPATEN PESISIR SELATAN - Muhammad Arif; Alexander Syam (STKIP Pesisir Selatan, 2017)
This descriptive qualitative reasearch was done in order to find out the development strategy for Sumedang Beach, a tourism site at Ranah Pesisir, Pesisir Selatan District. It was found that the maintenance of public facility around the beach was not mananaged as well as it should be. The accomodation was not enough provided. Moreover, the villagers did not have awareness toward tourism value of their environment. These facts were the bottom line reasons why the researcher conducted this research. The data was obtained by using observation, interview and documentation which were done with Tourism Ministry, Bappeda, villagers and their leaders. The data was analyzed by using SWOT Analysis (Strengths,Weaknes,Opportunities and Threats). The result of the research shown that Pesisir Selatan District need to do: 1) A Counseling for improving and enhancing villagerss awareness about the importance of an awaranesess toward tourism site;2) A Coordination with private sector to obtain an income;3) A Development toward tourism attractions; 4) An Improvement of public facility;5) A Development for tourisms accessibility.Keywords: the development strategy, tourism site, sumedang beach